2012
DOI: 10.5187/jast.2012.54.3.185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Garlic and Thyme Extracts on Growth Performance and Carcass Characteristics of Broiler Chicks

Abstract: A total of 800 one-day-old chickens (Cobb 500) were obtained from a local hatchery and allocated randomly to five dietary treatments. This study conducted for 42 d. Treatment groups included 1) CON (control), 2) T0.3 (0.3% of thyme extract), 3) T0.6 (0.6% of thyme extract), 4) G0.3 (0.3% of garlic extract) and 5) G0.6 (0.6% of garlic extract). Thyme extract included 90 μg/ml Carvacrol and 400 mg/ml thymol while garlic extract included 100 mg/ml elastin. There were no significant effects among the treatments on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
5
14
4
Order By: Relevance
“…In the present trial, coriander powder supplementation level had no effect (P >0.05) on the carcass traits. This result was in agreement with Case et al (1995), Botsoglou et al (2002), Jang et al (2007) and Amouzmehr et al (2012), who reported that the use of herbal plants had no effect on the dressing percentage of broiler chickens. …”
Section: Resultssupporting
confidence: 91%
“…In the present trial, coriander powder supplementation level had no effect (P >0.05) on the carcass traits. This result was in agreement with Case et al (1995), Botsoglou et al (2002), Jang et al (2007) and Amouzmehr et al (2012), who reported that the use of herbal plants had no effect on the dressing percentage of broiler chickens. …”
Section: Resultssupporting
confidence: 91%
“…Similar findings with respect to increased FCR were reported by earlier researchers [9,10,12,18,20,21]. In contrary to findings of this study, some authors observed that the supplementation of garlic and neem leaves had no significant (p>0.05) effect FCR [14,16,[22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 56%
“…These results are in agreement with earlier researchers [15,17,23,25,[27][28][29][30]. In the contrary with these findings, a significant increase in average dressing percentage with supplementation of garlic [18] and neem [9,11] was also reported by earlier workers in broilers.…”
Section: Discussioncontrasting
confidence: 54%
“…Highest final weight (290.2g) was observed in quails fed 3% PLMGPD followed by quails fed diet 4 with 280.1g, the lowest weight was recorded in quails fed diet 1 with 259.3g. This observation agrees with the views of Dieumou et al (2012) on the effect feeding ginger and garlic on the performance of broilers and Alagbe, J.O (2017) on the dietary inclusion of P. longifolia leaf meal as phytobiotic compared with antibiotics on broiler performance and contrary to the reports of Amouzmehr et al (2013); Botsoglu et al (2004); Kamal and Abo (2012) and Safa et al (2012). The higher weight recorded could be as a result of the synergistic combination of PLM + GLPD mixture which help to reduce disease pressure on the animals, thereby increasing the opportunity of the flock to achieve better FCR and improved performance.…”
Section: Discussioncontrasting
confidence: 56%